Classification of the Polytminae (Aves: Trochilidae) - Remsen, J. V. Jr.; Stiles, F. Gary; Mcguire, Jimmy A. (Zootaxa, 2015)
The subfamily Polytminae, as defined by Dickinson & Remsen (2013) using the phylogeny of McGuire et al. (2009), consists of 12 genera and 27 species of hummingbirds (Trochilidae) distributed widely in the Neotropics, including the Caribbean. McGuire et al. (2014) expanded greatly on the taxon- and gene-sampling in McGuire et al. (2009), and although the phylogeny presented therein indicated the need for several changes in classification, such changes were beyond the scope of that paper.